Šifrant padavinskih območij vodotokov Republike Slovenije - Šraj, Mojca (Acta hydrotechnica, 2001)
Proper water resources planning and management requires a simple, yet descriptive and comprehensive coding system for rivers and their watersheds. Different coding systems in Europe and the USA are discused in this paper, with an emphasis on a coding system developed for Slovenia. The coding system for Slovenia and its applicability are represented in greater detail.
Keywords: hidrologija; padavinska območja; povodje; Slovenija; šifrant; šifriranje